2020
DOI: 10.20344/amp.11465
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence in Healthcare: A Single-Center Study on Causes, Consequences and Prevention Strategies

Abstract: Introduction: Workplace violence is one of the main risk factors in the professional world. Healthcare workers are at higher risk when compared to other sectors. Our study aimed to characterize physical and verbal violence in a public hospital and to define occupational health prevention and surveillance strategies.Material and Methods: Single center observational cross-sectional study, carried amongst healthcare workers in a public hospital in Lisbon. A qualitative survey was carried out through six in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
(30 reference statements)
2
17
0
Order By: Relevance
“…Participants who suffered violence (556) were included in the network analysis with 16 variables: 7 sociodemographic and 9 related to the violence suffered. We identified that physical violence (8) was not associated with other types of violence. We noticed an association between psycho-verbal (9) and psycho-non-verbal (10).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Participants who suffered violence (556) were included in the network analysis with 16 variables: 7 sociodemographic and 9 related to the violence suffered. We identified that physical violence (8) was not associated with other types of violence. We noticed an association between psycho-verbal (9) and psycho-non-verbal (10).…”
Section: Resultsmentioning
confidence: 84%
“…Violence at work involving health professionals is a phenomenon that has been researched at an international level and, despite the attention it has been receiving, this topic still represents an important challenge. Studies highlight that health workers are at greater risk of suffering violence when compared to other professional sectors, and the worrying naturalization of this phenomenon reinforces the increase in occurrences and the personal consequences for health care activity [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Morken, Johansen, and Alsaker (2015) found that even nurses who reported an incident in the past often would not report again in the future due to the perception of nothing really happens and the report forms were placed at the bottom of a drawer. Most participants reported that they were not familiar with their hospital internal reporting procedures (Antao et al, 2020). Chen et al (2013) highlighted reasons for not reporting violent incidents including the following: no benefits were gained from reporting incidents; nurses did not want to avoid their job responsibilities and lack of time to complete a report.…”
Section: Underreporting Of Violencementioning
confidence: 99%
“…Nurses are at high risk of experiencing Workplace Violence (WPV) (Hegney, Tuckett, Parker, & Eley, 2010) compared to other sectors (Antao et al, 2020;Han et al, 2017). Chapman and Styles (2006) described the everyday reality of nurses facing episodes of violence and aggression while working in the Australian healthcare system.…”
Section: Introductionmentioning
confidence: 99%